Comparing Holmium (Ho): YAG Laser with Pneumatic Lithoclast for Treatment Efficacy of Ureteric Stones - Asadullah; Salman el Khalid; Waqar Ahmed Memon; Ali Haider; Adnan Siddiq Awan; Muhammad Bilal Quddus (ziauddin University, 2024)
Background: Holmium YAG (yttrium-aluminum-garnet) laser, a comparatively new technique, can clear all types and sizes of stones and is only being used in two institutes of Karachi, Pakistan. The study aimed to compare pneumatic lithoclast and holmium YAG laser, to evaluate stone-free rate (SFR), postoperative complications, operative duration, and effectiveness. Methods: This cross-sectional research included 60 patients with age 16-65 years having ureteric stones, reporting to kidney center, Urology Department, Karachi, Pakistan. CT Scan of Kidneys, Ureter, and Bladder (KUB) were used to record stone size, laterality, and location within the ureter. Patients were divided into two clusters of 30 each, group A (Ho: YAG laser) and group B (pneumatic Lithoclast) having 0.5 to 02 cm of size ureteric stones. An Independent two-sample "t" test was used to assess the difference for the continuous variables. A p-value of ≤0.05 was considered statistically significant. Results: Stone sizes distribution was 1.3±0.3cms and 1.4±0.3cms for A and B groups respectively (p=0.8). The insignificance of the p-value demonstrated no substantial divergence between both groups and stone sizes. Clearance from the proximal ureter was noted 26(84.6%) in group A and 41.7% in group B with (p<0.05). A reduced lithotripsy activation period of 30.8±3.7mins was associated with stone size (p<0.05). Conclusion: Holmium: YAG Laser had better stone-free rate (SFR), with 84% clearance than pneumatic. Improved and effective clearance reduces the risk of residual stones within a lesser time, required for getting back to normal life routines. Keywords: Lasers; Ureteric Stones; Ho: YAG Laser; Pneumatic Lithoclast; Kidney Stones.